Maximal Strength, Muscle Activation, and Bar Velocity Comparisons Between Squatting With a Traditional or Safety Squat Bar. (February 2021) - Vantrease, William C.; Townsend, Jeremy R.; Sapp, Philip A.; Henry, Ruth N.; Johnson, Kent D.
Abstract : Abstract: Vantrease, WC, Townsend, JR, Sapp, PA, Henry, RN, and Johnson, KD. Maximal strength, muscle activation, and bar velocity comparisons between squatting with a traditional or safety squat bar. J Strength Cond Res 35(2S): S1–S5, 2021—The purpose of this study was to compare strength, muscle activation, and bar velocity between the traditional (TRAD) and safety squat bar (SSB) back squat. Thirty-two men (21.94 ± 3.1 years, 1.78 ± 0.8 m, 81.7 ± 10.1 kg) volunteered to complete this randomized, crossover-design study. Subjects completed 2 separate 1 repetition maximum (1RM) sessions using either the TRAD or SSB. Subsequently, subjects completed 1 session of 3 repetitions at 65 and 85% of their 1RM for each squat condition (SSB & TRAD). Peak muscle activation of 7 muscles from the lower body and trunk was recorded through surface electromyography (EMG), and mean velocity (MV) was recorded by a linear transducer. Electromyography and MV were analyzed by a 2 × 2 (bar × load) repeated-measures analysis of variance. A Pearson correlation was used to determine the relationship of 1RM load between bars. Squat 1RM was significantly higher ( p < 0.001; 11.6%) for TRAD (144.7 kg) compared with SSB (128.8 kg), and a strong correlation ( r = 0.94) was observed between 1RM values of each bar. A significant main effect was seen in EMG ( p < 0.001) and MV for load ( p < 0.001). No significant bar × load interaction was observed between conditions for any EMG or bar velocity measure ( p > 0.05). The SSB produces similar muscle activation and bar velocities compared with the TRAD at relative intensities. However, absolute loads should be adjusted when changing squat bars during a training cycle.